Understanding Literacy Level in Vocational Schools in Padang Pariaman Regency - Putri, Hilma Pami (IdeBahasa, 2024)
Responding to the low interest among Indonesian students has prompted the government to formulate strategic policies to guarantee the future success of national education. One of the strategies is emphasizing the establishment of literacy programs at schools. This research is expected to see the execution of the program and find out the obstacles in handling the program. The subjects of this research were the literacy teams of the schools that consist of the administrators, the teachers, and the principals of the vocational schools in Padang Pariaman Regency. Ten schools, both private and public, were selected as the focus of this study. The data was collected through interviews and observations through the stages of implementing the literacy movement guidelines from Kemdikbud. The result showed that the literacy movement in Padang Pariaman regency was still at the habituation level and needed further government’ attention. The obstacles were found from the lack of the headmaster and the teams’ understanding in comprehending the movement. Hence, the government needs to do accompaniment to implement the program successfully.